DESAIN ULANG STASIUN LAYANG JUANDA SURABAYA DENGAN APLIKASI AUTODESK REVIT YANG MENGACU PADA PERATURAN MENTERI PERHUBUNGAN (FSTPT Indonesia, 2023)
The planning on the design of the Juanda Surabaya flyover station will aim to facilitate the movements of passengers from Surabaya City to Juanda airport and the other way around, also to reduce the number of passenger capacity at Juanda airport. In this research using the assistance of the Autodesk Revit application. In a survey conducted on the Juanda Airport area with the location point in front of the Juanda airport lobby. The land area required in the planning design of the Juanda Elevated Station is approximately 10,854 m2, and the available land area itself is 11,100 m2. The Juanda Surabaya Flyover Station will be designed with a class of small station class because the calculation of the credit points numbers that shows the result of small station class which refers to PM. 33 of 2011 Concerning to Types, Classes and Activities at Train Stations. The amount of rooms and the space size of the room are designed based on the Manual Book for Standardization of Railway Stations owned by PT. KAI in 2012 and based on PM. 29 of 2011 Concerning The Technical Requirements for Railway Station Buildings. ABSTRAK Perencanaan pada desain Stasiun Layang Juanda Surabaya akan bertujuan untuk mempermudah pergerakan penumpang dari Kota Surabaya menuju ke Bandara Juanda, begitu juga sebaliknya dan mengurangi jumlah kapasitas penumpang di Bandara Juanda. Dalam penelitian ini menggunakan bantuan aplikasi Autodesk Revit. Pada survei yang dilakukan di lahan Bandara Juanda dengan titik lokasi berada di depan lobby Bandara Juanda. Luas lahan yang dibutuhkan pada perencanaan desain Stasiun Layang Juanda adalah kurang lebih 10.854 m2, untuk lahan yang tersedia seluas 11.100 m2. Stasiun Layang Juanda Surabaya ini akan didesain dengan kelas stasiun kecil karena dari perhitungan jumlah angka kredit yaitu menunjukkan pada kelas stasiun kecil yang mengacu pada PM. 33 Tahun 2011 Tentang Jenis, Kelas dan Kegiatan Di Stasiun Kereta Api. Jumlah ruang dan besaran ruang di desain berdasarkan Buku Pedoman Standardisasi Stasiun Kereta Api milik PT. KAI Tahun 2012 dan berdasarkan PM. 29 Tahun 2011 Tentang Persyaratan Teknis Bangunan Stasiun Kereta Api.